Nitrogen Oxides Emissions, Chemistry, Deposition, and Export Over the Northeast United States During the WINTER Aircraft Campaign. Issue 21 (5th November 2018) - Jaeglé, L.; Shah, V.; Thornton, J. A.; Lopez‐Hilfiker, F. D.; Lee, B. H.; McDuffie, E. E.; Fibiger, D.; Brown, S. S.; Veres, P.; Sparks, T. L.; Ebben, C. J.; Wooldridge, P. J.; et al.
Abstract: We examine the distribution and fate of nitrogen oxides (NO x ) in the lower troposphere over the Northeast United States (NE US) using aircraft observations from the Wintertime INvestigation of Transport, Emissions, and Reactivity (WINTER) campaign in February–March 2015, as well as the GEOS‐Chem chemical transport model and concurrent ground‐based observations. We find that the National Emission Inventory from the U.S. Environmental Protection Agency is consistent with WINTER observations of total reactive nitrogen ( T NO y ) to within 10% on average, in contrast to the significant overestimate reported in past studies under warmer conditions. Updates to the dry deposition scheme and dinitrogen pentoxide (N2 O5 ) reactive uptake probability, ɣ(N2 O5 ), result in an improved simulation of gas‐phase nitric acid (HNO3 ) and submicron particulate nitrate (pNO3 − ), reducing the longstanding factor of 2–3 overestimate in wintertime HNO3  + pNO3 − to a 50% positive bias. We find a NO x lifetime against chemical loss and deposition of 22 hr in the lower troposphere over the NE US. Chemical loss of NO x is dominated by N2 O5 hydrolysis (58% of loss) and reaction with OH (33%), while 7% of NO x leads to the production of organic nitrates. Wet and dry deposition account for 55% and 45% of T NO y deposition over land, respectively. We estimate that 42% of the NO x emitted is exported from the NE US boundary layer during winter, mostly in the form of HNO3  + pNO3 − (40%) and NO x (38%). Plain Language Summary: Nitrogen oxides are a key family of pollutants emitted by cars, electric utilities, and industry. The fate of nitrogen oxides remains poorly understood especially during the winter season, when low sunlight leads to their persistence in the atmosphere. We analyze comprehensive aircraft observations of nitrogen oxides and their atmospheric products over the Northeast United States during winter 2015. This detailed chemical information allows to resolve a long‐standing overestimate of the oxidation products of nitrogen oxides and places new constraints on their deposition to land ecosystems and export to the global atmosphere. Key Points: Existing anthropogenic NO x inventory is consistent with aircraft and ground‐based observations over Northeast United States during winter NO x has a 22 hr lifetime, with half of NO y present as NO x, 37% as HNO3 and pNO3 −, and remaining 13% mostly as PAN Model reproduces NO y partitioning and predicts a 42% NO x export efficiency in winter, with a 55–45% split between wet and dry deposition